Design and Implementation of a Distributed Parameter Electromechanical System Control System for Automation and Optimization - A. P. Korneev; Yitong Niu; Muneer S.G. Mansoor; Zinah S. Jabbar; Jamal Fadhil Tawfeq; Ahmed Dheyaa Radhi (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
A distributed parameter electromechanical system control system is a type of control system that is used to control the operation of electromechanical systems. This type of system is designed to provide a high degree of accuracy and reliability in controlling the operation of an electromechanical system. It can be used to control a wide variety of systems, including motors, pumps, valves, and other types of machinery. Considering a system with distributed parameters of mechanical parts, this paper designs a method for implementing a semi-closed control system of electromechanical systems with distributed parameters of mechanical parts using an observation device. The observation device is in feedback and restores the output velocity without directly measuring it. For the observation device, a general view of the transfer function is determined, and its graphical representation is given. The LAFC of the mechanical part of the system with distributed parameters is presented, where the observation device with and without the experimental bench used for the simplest case is compared. Finally, a method of implementing a semi-closed control system for electromechanical systems with distributed parameters of mechanical parts using the observation device is presented.